Kompetensi Siswa dalam Menulis Teks Prosedur Menggunakan Metode Discovery Learning Siswa Kelas X SMK Swasta Eria Medan - Nurzannah Nauli Hasibuan; Putri Juwita (Universitas Islam Sumatera Utara, 2022)
This study aims to determine the ability to write procedural texts using the Discovery Learning method for the tenth grade students of Eria Medan Private Vocational School for the academic year 2021-2022. The population of class X students of the Eria Private Vocational School in Medan is 38 students consisting of two classes and for the research sample, one class is taken with 21 students.The method used in this research is the discovery learning method. The design of this research is to use classroom action research which consists of two cycles. Each cycle consists of planning, implementing actions, observing and reflecting. The subjects of this study were students of class X AKL at SMK Swasta Eria Medan which consisted of 21 students. This research was carried out in two stages, namely the first cycle and the second cycle in the form of the results of the procedure text writing skills in the form of a questionnaire. with the target of completeness the average value obtained is with a value of 75. From cycle I to cycle II the increase from the data proves that using the discovery learning method can improve the results of writing procedure texts for students. From the results of the overall data, it was found that 16 students were able to write procedural texts by getting a score of 75 and above from 21 students and 5 students who were unable to write procedure texts with a score of 70 and below. Thus, it can be said that the students of class X AKL at SMK Swasta Eria Medan were able to improve learning outcomes in writing procedural texts using the discovery learning method because the number of students' scores reached 70-100.Â This study aims to determine the ability to write procedural texts using the Discovery Learning method for the tenth grade students of Eria Medan Private Vocational School for the academic year 2021-2022. The population of class X students of the Eria Private Vocational School in Medan is 38 students consisting of two classes and for the research sample, one class is taken with 21 students.The method used in this research is the discovery learning method. The design of this research is to use classroom action research which consists of two cycles. Each cycle consists of planning, implementing actions, observing and reflecting. The subjects of this study were students of class X AKL at SMK Swasta Eria Medan which consisted of 21 students. This research was carried out in two stages, namely the first cycle and the second cycle in the form of the results of the procedure text writing skills in the form of a questionnaire. with the target of completeness the average value obtained is with a value of 75. From cycle I to cycle II the increase from the data proves that using the discovery learning method can improve the results of writing procedure texts for students. From the results of the overall data, it was found that 16 students were able to write procedural texts by getting a score of 75 and above from 21 students and 5 students who were unable to write procedure texts with a score of 70 and below. Thus, it can be said that the students of class X AKL at SMK Swasta Eria Medan were able to improve learning outcomes in writing procedural texts using the discovery learning method because the number of students' scores reached 70-100.